2011
DOI: 10.1007/s13277-011-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin mRNA target site selection for DNAzymes using secondary structure and hybridization thermodynamics

Abstract: Ezrin, a membrane organizer and linker between plasma membrane and cytoskeleton, is well documented to play an important role in the metastatic capacity of cancer cells especially for osteosarcoma cells. It has provided an ideal target for cancer gene therapy. RNA-cleaving 10-23 DNAzymes, consisting of a 15-nucleotide catalytical domain flanked by two target-specific complementary arms, can cleave the target mRNA at purine-pyrimidine dinucleotide effectively. In the present study, we designed and screened the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…[20], binds to ezrin resulting in inhibition of in vitro and in vivo cell migration, invasion, and metastatic colony survival. Wang et al [38] showed AU1751 to be the most effective target site of ezrin mRNA for DNAzymes. Pignochino et al [19] investigated sorafenib, showing its effectiveness in inhibiting osteosarcoma cell line proliferation, inducing apoptosis and downregulation of P-ERK1/2, MCL-1, and P-ERM.…”
Section: Discussionmentioning
confidence: 99%
“…[20], binds to ezrin resulting in inhibition of in vitro and in vivo cell migration, invasion, and metastatic colony survival. Wang et al [38] showed AU1751 to be the most effective target site of ezrin mRNA for DNAzymes. Pignochino et al [19] investigated sorafenib, showing its effectiveness in inhibiting osteosarcoma cell line proliferation, inducing apoptosis and downregulation of P-ERK1/2, MCL-1, and P-ERM.…”
Section: Discussionmentioning
confidence: 99%
“…Taking cancer research as an example, different DNAzymes designed for different kinds of mRNA genes, including the LMP1, b-integrin, Bcr-abl, uPAR, Survivin, Ezrin and k-ras genes for in vitro studies have been reported. [116][117][118][119][120][121] The DNAzymes designed demonstrated inhibition of either proliferation and metastasis, or adhesion and invasion. These studies also indicated that different cancer genes could be successfully down-regulated by DNAzymes no matter if they were cell-expressed or virusexpressed.…”
Section: Dnazyme Based Drug Delivery and Therapymentioning
confidence: 99%
“…Inhibiting proliferation [15] k-ras Enhancing radiosensitivity [16] Prostatic cancer Aurora kinase A Inhibiting proliferation and metastasis; promoting apoptosis; down-regulating telomerase activity [17] Epithelioma c-Jun Inhibiting proliferation; blocking angiogenesis; suppressing tumor growth [18] Leukocythemia Bcr-abl Inhibiting proliferation; enhancing success rate of autologous stem cell transplants [19] PML/RARα Inhibiting proliferation and vitality; promoting apoptosis [20] Liposarcoma c-Jun Promoting apoptosis; suppressing tumor growth [21] Osteosarcoma uPAR Inhibiting invasion [22] Ezrin Inhibiting proliferation [23] in the development of acute promyelocytic leukemia (APL). DNAzymes that cleave the PML/RAR transcripts were designed by Kabuli et al [20].…”
Section: 1-integrinmentioning
confidence: 99%